2009
DOI: 10.1051/0004-6361/200809582
|View full text |Cite
|
Sign up to set email alerts
|

The global rotation of solar activity structures

Abstract: Aims. This paper investigates the rotation rate of solar activity from a global point of view, considering daily index or flux, instead of individual structures. It determines the rotation rate variations inside the cycle by two-year sequences and the comprehensive study of the cycle. Methods. The method consists of harmonic analysis of series of daily monitoring of solar activity. One is the sunspot number covering cycles 9 to 23 (over 157 years) and the second the flux of the corona at 2800 MHz from cycle 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
(30 reference statements)
7
23
2
Order By: Relevance
“…The main difference between the two methods seems to be so that the best-fit solution now tends to emphasize the hemispheric difference, especially in the latitudinal variation parameter B, more strongly than earlier. This contradicts the result of Heristchi & Mouradian (2009), who found no north-south asymmetry in solar rotation. Large B values for both hemispheres strongly suggest that sunspot groups follow the differential rotation law, which differs from the conclusion of Balthasar (2007).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The main difference between the two methods seems to be so that the best-fit solution now tends to emphasize the hemispheric difference, especially in the latitudinal variation parameter B, more strongly than earlier. This contradicts the result of Heristchi & Mouradian (2009), who found no north-south asymmetry in solar rotation. Large B values for both hemispheres strongly suggest that sunspot groups follow the differential rotation law, which differs from the conclusion of Balthasar (2007).…”
Section: Discussioncontrasting
confidence: 92%
“…We found that the refined parameters describing the rotation of active longitudes are mutually consistent for the three flare classes and that the northern hemisphere rotates significantly faster than the southern hemisphere during the last three solar cycles. This contradicts the result of Heristchi & Mouradian (2009), who found no significant difference between the rotation rates of the two hemispheres. Moreover, the refined parameters yielded a consistently higher level of non-axisymmetry for the longitudinal distribution, thus increasing evidence for the existence of active longitudes.…”
Section: Introductioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The secular deceleration of solar rotation was suggested by Brajša et al (2006) and Li et al (2011), while a secular acceleration trend was found by Heristchi & Mouradian (2009). A north-south asymmetry in solar rotation has been reported by many authors Balthasar et al 1986;Antonucci et al 1990;Rybák 1994Rybák , 2000Brajša et al 1997Brajša et al , 2000Javaraiah 2003;Georgieva et al 2005;Mursula & Hiltula 2004;Gigolashvili et al 2007;Zaatri et al 2009;Wöhl et al 2010), but there is so far no agreement on which of the two hemispheres is rotating faster, or how the difference between the hemispheric rotation rates is changing in time.…”
Section: Introductionmentioning
confidence: 93%
“…Changes in the solar rotation were also investigated by the helioseismological method using the GONG and SOHO-MDI data at the base of the convective zone (Howe et al 2000a(Howe et al ,b, 2001) and at high latitudes (Antia & Basu 2001). Recently, the time-series analysis was applied to investigate temporal changes of the solar rotation, especially using the radio data (Heristchi & Mouradian 2009;Chandra et al 2009). Various frequencies correspond to various altitudes in the solar corona and different methods have been used (e.g., the Sun analysed as a star with no latitudinal dependence, autocorrelation analysis with a time lag, etc.).…”
Section: Introductionmentioning
confidence: 99%